A Short History of the Liberal Party - Cook, C. author. aut Link
VII, 363 p.
Keywords: Chris Cook lifts the lid on the 'third Party; ' charting their fascinating journey over the last century, from the landslide victory of 1906 under Asquith, via their descent into divisions and decline in the interwar years, to in-depth analysis of the 2010 British Election and their return to Government in the Conservative-Lib Dem coalition.